The revisited role of investor sentiment for equity value - Büning, Leopold Hubertus (2022)
This paper contrasts traditional asset pricing models with the assumptions of behavioural finance and investigates the asset valuation explanatory power of investor sentiment. Therefore, we extend the Fama-French-4-Factor model by another factor controlling for sentiment. We consider different portfolios segmented by the firm characteristics size, value (book-to-market) and volatility. Even though the revised factor model does not improve the predictive power, our segmentation sheds light on the cross-section of stock return by examining stocks sensitivities to changes in beginning-of-period sentiment. The empirical model confirms our predictions that smaller, more volatile and growth stocks are more affected by sentiment changes.